Functioning of Intertextemes of Biblical Origin in Modern Orthodox Prose (by Material of O. L. Rozhneva’s Stories-Parables) - P. A. Kolobaev (Научный диалог)
The features of intertextemes of biblical origin functioning in the church-religious discourse on the material of O. L. Rozhneva’s stories-parables are considered. The relevance of the study is determined by the importance of studying the church-religious style, biblical themes, genre features of a story-parable. Through the use of a combination of literary and linguistic-cultural methods, the phenomenon of O. L. Rozhneva’s creativity and its place in modern Orthodox literature is revealed. The novelty of the study is seen in the author’s appeal to the previously unexplored texts of Orthodox fiction. Classification of types of intertextemes of biblical origin is proposed: intertextuality as co-presence in the same text of two or more texts (quotation, allusion, plagiarism, etc.), paratextuality as the relation of text to its title, afterword, epigraph, architextuality understood as a genre link of texts. The following functions of intertextemes of biblical origin in O. L. Rozhneva’s prose are distinguished: text formation and didactic / educational / moral; which, in turn, is divided into the comforting, claiming in faith and anagogical (that raises man above the world of mortal reality). With the help of illustrative material identification as a type of O. L. Rozhneva’s relation to the biblical text is characterized. It is proved that for this purpose the modern writer uses archetypal plots (repentant sinner, miracle of healing, prayerful help, among “own” - “alien” worlds, righteous persons, fruit of belief, a way to God, kind pastor, roads of life, etc.).